2018
DOI: 10.1177/0748730418783651
|View full text |Cite
|
Sign up to set email alerts
|

Musicians’ Natural Frequencies of Performance Display Optimal Temporal Stability

Abstract: Many human action sequences, such as speaking and performing music, are inherently rhythmic: Sequence events are produced at quasi-regular temporal intervals. A wide range of interindividual variation has been noted in spontaneous production rates of these rhythmic action sequences. Dynamical theories of motor coordination suggest that individuals spontaneously produce rhythmic sequences at a natural frequency characterized by minimal energy expenditure and maximal temporal stability, relative to other frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
88
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(102 citation statements)
references
References 34 publications
13
88
1
Order By: Relevance
“…In another study, musician performed a melody in a solo setting without a metronome, starting at spontaneous tempo that was slower or faster than the SMT. Results showed that the musician's tempo had a tendency to drift back to the SMT [5]. This tendency to drift back to the SMT has also been observed in other similar studies [96,101].…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…In another study, musician performed a melody in a solo setting without a metronome, starting at spontaneous tempo that was slower or faster than the SMT. Results showed that the musician's tempo had a tendency to drift back to the SMT [5]. This tendency to drift back to the SMT has also been observed in other similar studies [96,101].…”
Section: Introductionsupporting
confidence: 84%
“…3.3A). Their results show that musicians had a tendency to return to their SMT during a simple melody performance that started at a tempo di↵erent than their SMT [5]. ASHLE does not produce pitch, but we can use it to simulate the beats during this music performance task.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations